Proses Berpikir Kreatif Proses Berpikir Kreatif Siswa SMP Bergaya Kognitif Impulsif dan Reflektif dalam mengajukan masalah matematika - syifaul Qulub (Program Studi S1 Matematika UNESA, 2020)
Problem posing can be used to see creative thinking skills. In posing a problem, each student has a different way of thinking, because the way students process the information they receive is different. This difference is known as cognitive style. Cognitive styles that are based on time differences and students' accuracy in responding to something can be divided into two, namely impulsive and reflective cognitive styles. The purpose of this research is to describe the creative thinking process of junior high school students with impulsive and reflective cognitive style in posing mathematical problems. The method used is descriptive method with a qualitative approach. Based on the results of the MFFT test and the TPM test, two research subjects were obtained, namely one impulsive cognitive style subject and one reflective cognitive style subject. The results showed that the creative thinking process of students with impulsive cognitive style in posing mathematical problems, namely: the stage of synthesizing ideas, the subject reads information, concludes the problem then remembers the experience of working on relevant questions, the subject does not require a long time at this stage; in the idea building stage, the subject relates the experience of working on a problem with the information on the test so that the subject can create an idea; in planning the implementation stage, the subject makes a question framework based on the ideas obtained, namely the purchase of goods in packages; the stage of implementing the idea, the subject applies the idea that has been obtained. The subject re-checks the questions and solutions to check whether they are correct. The subject believes that the problems and solutions made are correct. The creative thinking process of the subject in a reflective cognitive style in posing a mathematical problem, namely: the stage of synthesizing an idea, the subject repeatedly reads the test to understand the information then remembers the experience of working on the relevant questions, the subject takes quite a long time at this stage; the idea building stage, the subject associates the experience he has with the information on the test so that the subject can make more than one idea; the stage of planning the implementation, the subject chooses an idea that he feels can solve it, the subject uses a textbook as a reference in making questions, the subject makes questions about purchasing items that are separate from the package; the stage of applying the idea, the subject applies the idea that has been selected, the subject can make two questions. The subject re-checks the questions and solutions made to check whether they are correct. The subject believes that both the problems and the solutions made are correct.